Pelatihan dan Pengembangan Desain Produk Batik Tulis dalam Upaya Peningkatan Ketrampilan dan Merespon Peluang Pasar - Rahayu; Armin , Rini; Tri Asmorowati, Erna (Fakultas Ekonomi Universitas Islam Majapahit, 2024)
The purpose of fostering of developing small and medium businesses for the group of batik activists in Kudubanjar Village, District. Kudu, Kab. Jombang in the form of product design development training carried out by the PPA Service (Child and Women's Protection Service) is to improve skills in making variations in batik product designs, train batik activists to be responsive to market interests while increasing the ability of batik activists to read market opportunities. The training was attended by 55 batik activists consisting of: 1) female home workers (batik activists), and 2) female cadres. The training implementation method was carried out using the lecture method, practice of making written batik t-shirts and questions and answers. The results of the training include 1) The training participants have demonstrated basic skills in batik t-shirt making techniques, 2) The participants have the ability to develop new ideas for product differentiation, 3) The participants are enthusiastic about knowing and implementing appropriate marketing strategies to respond to various market segments batik.